KHAMID OLIMJON, ONE OF THE RESEARCHERS WHO STUDIED FITRAT - Dilnoza Jumaeva (American Journals Publishing, 2023)
This article contains the analysis of the research about Fitrat’s literary work written by the famous Uzbek poet and scientist Hamid Olimjon in 1936, and it also contains the fact that the poet is thought to be the first who researched Fitrat.
Keywords: Khamid Olimjon, Abdurauf Fitrat, jadids, bourgeois literature, dramas by Fitrat, cultural poverty, science and education.